Jerzy Potocki w kręgu polityki - Jankowiak, Krzysztof (Instytut Kultury Europejskiej UAM w Gnieźnie oraz Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The paper covers the first half of the 20th century, a period of decline in the history of aristocracy, Polish aristocracy in particular. The article is concerned chiefly with count Jerzy Potocki, from the Łańcut branch of the family. It aims to determine the state of knowledge about his relationships with broadly understood politics, including his own political activities in different domains. The basis for the analyses is provided chiefly by various publications, at times including data from unpublished archival sources. The analyses demonstrate the diversification of knowledge and advisability of further research, particularly with archival sources.
JERZY POTOCKI IN THE CIRCLES OF POLITICS
Summary: In the first half of the 20th century, the leading position and the role of aristocracy in European realities drew to a close, also in foreign policy, which thus far had been its special domain. Nevertheless, representatives of aristocracy, moulded in its proper spirit and tradition and still upholding its values and standards, would be closely associated with politics, also as active participants. Count Jerzy Potocki, a member of the Łańcut branch of Poland’s leading aristocratic family, was such a person. Since the beginning, his associations with politics have been a matter of interest and varied accounts and statements, which produced a certain body of knowledge on that topic. The knowledge has not been comprehensively studied and presented, hence this paper attempts to determine its nature and the current state, based chiefly on pertinent publications. This goal is pursued through an analysis of statements that the publications quote. The statements concern the social and cultural background in which Potocki was brought up, in which he was confronted with varied manifestations and forms of political life and which lay the foundations of his approach to that particular area. There is no shortage of references to the relevant personal predispositions and abilities, as well as to skills in acquiring those. The publications shed light on the initial contacts with the political sphere and the resulting experience. There are also accounts which reveal the relationships associated with young Potocki’s service in the Austrian-Hungarian army, his participation in the Great War as well as the diverse nature of these relationships, which to a notable extent was expressed through specific activities. The written sources also recount his service in the Polish army and the contribution to the struggle for independence, made in close association with e.g. Józef Piłsudski and his political circles, and discuss how these relationships continued, affecting his later political attitudes and actions. Those activities which were concerned with the national matters and internal policy, such as social, organisational or parliamentary contribution tend to be mentioned in the passing or noted rather than described. Contrariwise, the matters of foreign policy and Potocki’s activities in that field, especially contributions in diplomacy are discussed at length. In turn, only incidentally does one read that having abandoned active political life after 1940, Potocki was associated with the diplomatic services of the Order of Hospitallers and had to deal with the authorities of the People’s Republic of Poland. The information in the published accounts is sometimes supplemented with data from unpublished archival sources, e.g. the memoirs of Jerzy Potocki. All accounts yield a vivid image of Jerzy Potocki as a “man of politics”. They reveal the multiplicity and diversity of his associations with the political sphere as well as the varied extent of knowledge about those – from a vague notion about some to a relatively comprehensive information about others. The causes and the circumstances, the mutual influences and references or ramifications are exposed only in part. If only for this reason, it would be sensible to study the issue further, as even at this stage it requires resorting to archival resources, not only in the country.
Keywords: JERZY POTOCKI; POLISH ARISTOCRACY; POLISH INTERNAL POLICY; INTERNATIONAL RELATIONSHIPS; POLISH FOREIGN POLICY